2021
DOI: 10.1097/md.0000000000025633
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of brain connectivity in neurologically asymptomatic patients with chronic kidney disease

Abstract: Our previous study demonstrated that patients with end-stage renal disease had decreased structural and functional brain connectivity, and there was a significant association between brain connectivity and cognitive function. The aim of this study was to evaluate the alterations of structural and functional connectivity using graph theoretical analysis in neurologically asymptomatic patients with relatively early-stage chronic kidney disease (CKD). We enrolled 18 neurologically asymptomatic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In this study, glymphatic system dysfunction was suggested even in patients with early CKD without neurological problems. In addition, alterations of structural connectivity, accounting for information processing of neural networks, in the brains of patients with early CKD have also been observed in our previous study (20). These results suggest that alterations in structural connectivity begin relatively earlier than functional alterations in CKD patients.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, glymphatic system dysfunction was suggested even in patients with early CKD without neurological problems. In addition, alterations of structural connectivity, accounting for information processing of neural networks, in the brains of patients with early CKD have also been observed in our previous study (20). These results suggest that alterations in structural connectivity begin relatively earlier than functional alterations in CKD patients.…”
Section: Discussionsupporting
confidence: 82%
“…Our previous study using graphic theoretical analysis showed that patients with ESRD had decreased structural and functional brain connectivity, and there was an association between brain connectivity and cognitive function ( 20 ). There were even changes in structural connectivity in asymptomatic patients with early chronic kidney disease (CKD) ( 21 ). In addition, cognitive decline in patients with ESRD improved after kidney transplantation ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) affects almost 15% of the global population [91]. Complications include cardiovascular diseases (CVDs), diabetes, hypertension, anemia, renal disease progression, acute kidney injury, mineral and bone disorders [92], and cognitive decline [93][94][95][96]. The kidney controls body fluid composition by filtering and reabsorbing materials.…”
Section: Kidney and Livermentioning
confidence: 99%